Sequential administration of vinorelbine plus cisplatin and bevacizumab followed by docetaxel plus gemcitabine and bevacizumab compared to docetaxel plus cisplatin and bevacizumab regimen as first-line therapy for advanced or metastatic non-squamous non-small cell lung cancer: A multicenter randomized phase II trial of the Hellenic Oncology Research Group (HORG). Issue 1 (April 2015) - Kotsakis, A.; Kentepozidis, N.; Emmanouilidis, Ch.; Polyzos, A.; Agelidou, A.; Vaslamatzis, M.; Chandrinos, V.; Agelaki, S.; Vamvakas, L.; Kalbakis, K.; Katsaounis, P.; Stoltidis, D.; et al.
Highlights Platinum-based chemotherapy is considered the cornerstone of treatment for NSCLC. Bevacizumab with sequential chemotherapy is feasible with manageable toxicity. This regimen in some cases is very active and leads to durable responses.